A critical participatory pedagogical approach to enabling life orientation students to develop social literacy through HIV education. Issue 2 (3rd April 2018) - Brown, Anthony; Wood, Lesley
Abstract : HIV education is an important component of the life orientation curriculum, since an intersectional understanding of HIV provides an entry point to appreciate the interrelatedness of various social injustices. Yet, our interaction with predominantly white and privileged pre-service life orientation students led us to believe that they did not perceive HIV education as something that was relevant to their personal or professional lives. Their rigid, stigmatising belief systems and "othering" attitudes prevented them from embodying the inclusive and life-enhancing values that life orientation is supposed to develop. This paper explains how we used iterative cycles of reflection and action to enable 86 student teachers of life orientation to interrogate their misconceptions about HIV education and its applicability for their professional and personal contexts. Students were able to acknowledge their prejudices and privileges, which in turn created a willingness to engage with HIV education and to embody their learning to bring about change in their daily interactions. The knowledge generated from this study indicates how a critical, participatory pedagogical approach to HIV education can develop the social literacy of students to enable them to live out the life-enhancing values that underpin the life orientation curriculum.